Assessment of acquired hemophilia patient demographics in the United States: the Hemostasis and Thrombosis Research Society Registry. Issue 7 (October 2016) - Kessler, Craig M.; Ma, Alice D.; Al-Mondhiry, Hamid A.B.; Gut, Robert Z.; Cooper, David L.
Abstract : The Hemostasis and Thrombosis Research Society (HTRS) Registry was used to monitor the postapproval use of recombinant factor VIIa. The objective of this manuscript is to provide key insights on the demographics of patients with acquired hemophilia in the HTRS Registry. Acquired hemophilia patient registration in HTRS captured age; sex; comorbidities and predisposing conditions; first bleeding location; laboratory parameters; exposure to blood products, factor, and bypassing agents; and initiation of immune suppression/tolerance therapy. Overall, 166 patients with acquired hemophilia were registered in HTRS (83 women, 73 men, median age 70 years); the majority were non-Hispanic whites (61.4%). The most common comorbidities were autoimmune disease (28.4%) and malignancy (14.5%). The most common first site of bleeding was subcutaneous (27.1%); this was more common in whites (29.1%) than blacks (12.5%) and in non-Hispanics (26.4%) than Hispanics (11.8%). Blood product exposure was reported for 33.1% of patients; the most commonly reported product was packed red blood cells (28%). Of the 57 patients with outcome data available for immune tolerance therapy, 26 patients (46%) reported successful treatment, 13 reported unsuccessful treatment (23%), and 18 (32%) were receiving active treatment at the time of registration. The HTRS Registry final analysis provides the only current comprehensive look at acquired hemophilia in the US population, including details on underlying autoimmune diseases and malignancies. Pertinent to recognition and diagnosis of the disease, subcutaneous bleeding as a presenting bleeding symptom was more common in white and non-Hispanic individuals.